Developing shared understandings of recovery and care: a qualitative study of women with eating disorders who resist therapeutic care. Issue 1 (December 2016) - Musolino, Connie; Warin, Megan; Wade, Tracey; Gilchrist, Peter
Abstract Background This paper explores the differing perspectives of recovery and care of people with disordered eating. We consider the views of those who have not sought help for their disordered eating, or who have been given a diagnosis but have not engaged with health care services. Our aim is to demonstrate the importance of the cultural context of care and how this might shape people's perspectives of recovery and openness to receiving professional care. Method This study utilised a mixed methods approach of ethnographic fieldwork and psychological evaluation with 28 women from Adelaide, South Australia. Semi-structured interviews, observations, field notes and the Eating Disorder Examination were the primary forms of data collection. Data was analysed using thematic analysis. Results & Discussion Participants in our study described how their disordered eating afforded them safety and were consistent with cultural values concerning healthy eating and gendered bodies. Disordered eating was viewed as a form of self-care, in which people protect and 'take care' of themselves. These subjectively experienced understandings of care underlie eating disorder behaviours and provide an obstacle in seeking any form of treatment that might lead to recovery. Conclusion A shared understanding between patients and health professionals about the function of the eating disorder may avoid conflict and provide a pathway to treatment. These results suggest the construction of care by patients should not be taken for granted in therapeutic guidelines. A discussion considering how disordered eating practices are embedded in a matrix of care, health, eating and body practices may enhance the therapeutic relationship.